Crop response to residual effects of basic slag, aggregate size and groundwater level treated acid sulfate soils - Manjur, Monija; Hossain, Sonia; Khan, Md Harunor Rashid (Dhaka University Journal of Biological Sciences, 2018)
A pot experiment with two acid sulfate soils of Badarkhali and Cheringa series were performed. After 18 years of fallow period in 2016, a crop trial was done in order to evaluate the response of rice plant without giving additional treatments. The average maximum temperature during the experimental period was 33.2ºC and average rainfall was 57 mm. Two cultivars of rice BRRI 48 and BRRI hybrid dhan 06 showed the tallest plant height of 115 cm and tillers 6.31 in numbers/plant on an average in both the soils. Panicle length was 16.5 cm, 1000-grain weight 22 g, grain yield 4.72 g/m2 and harvest index was 0.01 on average in both the soils. The experiment indicates that soil condition for crop growth possesses good quality after a long time and growth and yield parameters found satisfactory and significant (p ≤ 0.05). Dhaka Univ. J. Biol. Sci. 27(2): 113-123, 2018 (July)